2019
DOI: 10.1002/biof.1579
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: microRNA‐29b inhibits cell growth and promotes sensitivity to oxaliplatin in colon cancer by targeting FOLR1

Abstract: The present study was aimed to explore the functional role of microRNA (miR)-29b in colon cancer, as well as underlying mechanisms. Expressions of miR-29b and folate receptor 1 (FOLR1) were measured in both human colon tumor samples and cell lines.Colon cancer cell lines SW480 and SW620 were transfected with miR-29b mimic, antisense oligonucleotides (ASO)-miR-29b, small interfering (siRNA) against FOLR1 (si-FOLR1), or corresponding negative controls (NCs), and then were incubated with or without oxaliplatin (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The decrease in microRNA-29b expression has also been reported in other types of tumors (Sur et al 2019, He et al 2020, Fu et al 2020, however, only the study by Li et al 2017, had the expression of this microRNA in cervical samples was evaluated. Despite not considering all histopathological levels of cervical carcinogenic progression, they observed that the expression of microRNA-29b was suppressed when compared to normal tissues, corroborating our results.…”
Section: Discussionmentioning
confidence: 73%
“…The decrease in microRNA-29b expression has also been reported in other types of tumors (Sur et al 2019, He et al 2020, Fu et al 2020, however, only the study by Li et al 2017, had the expression of this microRNA in cervical samples was evaluated. Despite not considering all histopathological levels of cervical carcinogenic progression, they observed that the expression of microRNA-29b was suppressed when compared to normal tissues, corroborating our results.…”
Section: Discussionmentioning
confidence: 73%
“…MiR-132 is capable of significant reduction in the viability and proliferation of renal carcinoma cells [35]. These studies highlight this fact that identification of miRs and their subsequent targeting is a promising strategy in treatment of cancer as a life-threatening condition [36].…”
Section: Introductionmentioning
confidence: 79%
“… 30 , 31 Fu et al also demonstrated that FOLR1 expression promotes chemotherapy resistance. 32 Downregulation of FOLR1 significantly inhibited cell viability, enhanced sensitivity to oxaliplatin, and promoted cell apoptosis. The mechanism of chemotherapy resistance through stabilizing MDM2 in cooperation with chaperone protein prohibitin 2 was noted in FOLR1 expressing gastric cancer cells.…”
Section: Discussionmentioning
confidence: 98%